A mapping of labor mobility costs in the developing world - Artuc, Erhan (2015)
Estimates of labor mobility costs are needed to assess the responses of employment and wages to trade shocks when factor adjustment is costly. Available methods to estimate those costs rely on panel data,which are seldom available in developing countries.We propose a method to estimatemobility costs using readily obtainable data worldwide. Our estimator matches the changes in observed sectoral employment allocations with the predicted allocations froma model of costly labor adjustment.We estimate aworldmap of labormobility costs andwe use those estimates to explore the response of labor markets to trade policy.